2021
DOI: 10.1088/1755-1315/913/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Organic Fertilizer Enhanced Growth, Yield and Carotenoid Content of Carrot Plants (Daucus carota L.) Cultivated in the Lowland

Abstract: Carrot is an increasingly important root vegetable in Indonesia, and it is commonly served as cooked mixed-vegetables or consumed freshly as salads or juices. Therefore, development of eco-friendly cultivation technology, including in lowlands, is important to meet the increased demand. This research analysed growth and yield of carrot plant in lowland in response to foliar-organic-fertilization as well as characterized the quality, carotenoid and sugar contents as well as hardness of the taproot. A Randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This experiment was carried out in a greenhouse with irrigation on garden soil. It was established that the 30 tonne/ha vermicompost boosts soil fertility and promotes good crop development, especially for beetroot plants.In [12],author's have concluded that we can infer that carrots are a root vegetable that are mostly used in juices, salads, etc. Their demand is rising globally on a daily basis, thus crop output needs to expand to keep up.…”
Section: Litrature Survey Earliermentioning
confidence: 99%
“…This experiment was carried out in a greenhouse with irrigation on garden soil. It was established that the 30 tonne/ha vermicompost boosts soil fertility and promotes good crop development, especially for beetroot plants.In [12],author's have concluded that we can infer that carrots are a root vegetable that are mostly used in juices, salads, etc. Their demand is rising globally on a daily basis, thus crop output needs to expand to keep up.…”
Section: Litrature Survey Earliermentioning
confidence: 99%
“…This experiment was carried out in a greenhouse with irrigation on garden soil. It was established that the 30 tonne/ha vermicompost boosts soil fertility and promotes good crop development, especially for beetroot plants.In [12],author's have concluded that we can infer that carrots are a root vegetable that are mostly used in juices, salads, etc. Their demand is rising globally on a daily basis, thus crop output needs to expand to keep up.…”
Section: Litrature Survey Earliermentioning
confidence: 99%